Islamic Education and Globalization: Curriculum, Identity, and Digital Integration - Malizal, Zelynda Zeinab (Sinergi International Journal of Islamic Studies, 2025)
In an increasingly globalized world, Islamic education systems are under pressure to evolve while maintaining their core values. This narrative review explores how Islamic educational institutions respond to global educational trends through curriculum reform, digital integration, gender-inclusive leadership, identity formation, and international comparisons. The study employs a narrative synthesis methodology to analyze current empirical and conceptual literature, drawing on sources from diverse geographical and cultural contexts. The findings demonstrate that Islamic education is gradually aligning with global pedagogical practices, particularly through competency-based curriculum reforms, digital learning tools, and interdisciplinary approaches. Institutions are increasingly adopting interactive teaching models and integrating critical thinking into religious studies. However, systemic challenges—such as bureaucratic inertia, inadequate funding, cultural conservatism, and limited professional training—continue to hinder comprehensive transformation. The discussion highlights the need for adaptive policies, cross-sector collaboration, and inclusive strategies that balance tradition with innovation. This study underscores the importance of evidence-based interventions, including teacher training, leadership development, digital infrastructure, and curriculum adaptability. It concludes that sustainable reform in Islamic education hinges on the successful integration of global best practices with local cultural and religious values.